The forms of realization of constitutional and legal policy: theoretical and methodological analysis - Ternavska, Viktoriia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2019)
The article is dedicated to the research of legal nature of the juridical category «constitutional andlegal policy»and forms of its realization. Substantiation of a necessity of introducing a new category “constitutional and legal policy” into the system of the science of constitutional law, which forms of realization have not only theoretical but also practical significance for jurisprudence, is the purpose of this investigation. Successful realization of legal policy in practice, that is achievement of the goals and implementation of the tasks set by the state, requires its embodiment in the appropriate forms. The notion “form of realization of legal policy” is analyzed, which is considered not in the sense “source” by analogy with the form of law, but in the sense of the directions of its realization. Such basic, interdependent and close stipulated, forms of legal policy as doctrinal, law-making, law-enforcement, law-interpreting, law-educatingare defined. The inconsistency of the constitutional and legal reforms’ results, that have taken place over the past two decades, with the public expectations induces to revise the principles and forms of state policy production, including in the field of law. The formation and realization of the constitutional and legal policy of Ukraine requires, unlike other types of legal policy, not only the qualified practical activity of state and local self-government bodies, but also the active participation of civil society institutions. It is concluded that the formation of the qualitative constitutional and legal policy and its effective realization in the process of constitutional construction are conditioned by fruitful cooperation of the subjects of legal policy during a successive transition from one form of legal policy to another one. The theoretical foundations of the mechanism of realization of each form of legal policy should be provided both at the general theoretical and sectoral level. Thus, the development of all the above-mentioned directions of realization of legal policy, which should have theoretical and applied character, is the immediate task of the science of constitutional law.